2015
DOI: 10.1002/ejsp.2117
|View full text |Cite
|
Sign up to set email alerts
|

Grolar bears, social class, and policy relevance: Extraordinary agendas for the emerging 21st century

Susan T. Fiske

Abstract: This Agenda article first considers whether social psychology is in the best or worst of times and suggests that we are instead in extraordinary times, given exciting agendas and potential policy relevance, if we are careful. The article illustrates with two current research agendas—the hybrid vigor of multiple categories and the psychology of social class—that could inform policy. The essay then reflects on how we know when our work is indeed ready for the public arena. Regarding hybrids: World immigration, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
2
11
0
1
Order By: Relevance
“…In this vein, the evidence of these studies is absolutely in line with Fiske's (2015) agenda stressing multiple categorization as one of the crucial social cognitive means through which social psychology can help addressing the issues raised by hybrid and poly-cultural societies in our changing world. This might not be necessarily only related to Black people, but to other minority or ethnic groups towards whom people hold dehumanizing prejudice (e.g., Roma; Muslims).…”
Section: Practical Implications and Applicationssupporting
confidence: 58%
See 1 more Smart Citation
“…In this vein, the evidence of these studies is absolutely in line with Fiske's (2015) agenda stressing multiple categorization as one of the crucial social cognitive means through which social psychology can help addressing the issues raised by hybrid and poly-cultural societies in our changing world. This might not be necessarily only related to Black people, but to other minority or ethnic groups towards whom people hold dehumanizing prejudice (e.g., Roma; Muslims).…”
Section: Practical Implications and Applicationssupporting
confidence: 58%
“…While previous studies have shown that people tend to consider outgroup members as endowed with lesser humanity (Vaes et al, 2012), findings of this contribution consistently highlight that by processing multiple categorical information (Albarello & Rubini, 2015;Crisp & Hewstone, 2007;Fiske, 2015;Kang & Bodenhausen, 2014) the perception of outgroupers' humanity is enhanced at the implicit level of attribution of uniquely human emotions and, in turn, at the explicit level of attribution of human rights.…”
Section: Theoretical Implicationssupporting
confidence: 47%
“…We know relatively little about the social psychology of social class (Bullock, Lott, & Truong, ; Fiske, ; Williams, ) and much less about how the Great Recession affects the relations between groups and individuals. Some pioneering attempts had previously gathered work on the psychology of social class, some in the Journal of Social Issues (JSI) .…”
Section: Social Class the Great Recession And Social Psychology: Thmentioning
confidence: 99%
“…The millions of people around the globe who are in contact with foreign cultures through television and the Internet while still interacting with their own culture are a prime example of such change. The phenomena of globalization and immigration have the potential to increase contact among people from different cultures (Moghaddam, 2012) and aid in the creation of new hybrid forms of social identities (Fiske, 2015), possibly triggering the reorganization of their self-concept and the integration of new social and cultural identities (e.g., Amiot, de la Sablonnière, Terry, & Smith, 2007;Breakwell, 1986Breakwell, , 1988Jensen, Arnett, & McKenzie, 2011).…”
mentioning
confidence: 99%